Reply to the 'Comment on "Unprecedented 30 K hysteresis across switchable dielectric and magnetic properties in a bright luminescent organic–inorganic halide (CH6N3)2MnCl4"' by M. Szafrański, J. Mater. Chem. C, 2020, 8, 2594. Issue 35 (19th August 2020) - Sen, Abhijit; Swain, Diptikanta; Guru Row, Tayur N.; Sundaresan, A.
Abstract : In this response, we address the comments of Szafranski ( J. Mater. Chem. C, 2020, DOI: ; 10.1039/c9tc03552d ) on our paper on the thermal, dielectric and structural properties of (CH6 N3 )2 MnCl4 ( J. Mater. Chem. C, 2019, 7, 4838). Abstract : In this response, we address the comments of Szafranski ( J. Mater. Chem. C, 2020, DOI: ; 10.1039/c9tc03552d ) on our paper on the thermal, dielectric and structural properties of (CH6 N3 )2 MnCl4 ( J. Mater. Chem. C, 2019, 7, 4838). We discuss the discrepancies of the thermal, thermodynamic and dielectric parameters stated in both reports. The room temperature disordered structure as obtained from the refinement protocol suggested for disordered atoms by Sheldrick in the SHELXL programme is in good agreement, suggesting the split atom model.